The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/obr.13005
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines: A gear shift in puberty

Abstract: In this review, we discuss the role of adipokines in the onset of puberty in children with obesity during adrenarche and gonadarche and provide a clear and detailed overview of the biological processes of two major players, leptin and adiponectin. Adipokines, especially leptin and adiponectin, seem to induce an early onset of puberty in girls and boys with obesity by affecting the hypothalamic-pituitarygonadal (HPG) axis. Moreover, adipokines and their receptors are expressed in the gonads, suggesting a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 80 publications
(184 reference statements)
0
35
1
6
Order By: Relevance
“…Some epidemiological studies have found sex related differences but do not show a consistent pattern since some of the studies find associations in boys whereas others do in girls [37,38]. It is also possible that boys have a different response to a proinflammatory diet at a similar age since boys start sexual development later than girls and that adiposity distribution is different, being the third adipose rebound first in girls (10 years) than in boys (11-12 years) [39,40]. Other factors such as the effects of hormones and fetal and early-life exposures could determine later gender dependent responses as suggested by animal models and some epidemiological studies [3,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiological studies have found sex related differences but do not show a consistent pattern since some of the studies find associations in boys whereas others do in girls [37,38]. It is also possible that boys have a different response to a proinflammatory diet at a similar age since boys start sexual development later than girls and that adiposity distribution is different, being the third adipose rebound first in girls (10 years) than in boys (11-12 years) [39,40]. Other factors such as the effects of hormones and fetal and early-life exposures could determine later gender dependent responses as suggested by animal models and some epidemiological studies [3,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is implicated with the onset of puberty and related disorders in human females [ 139 ]. Leptin also directly or indirectly regulates GnRH secretion through Kisspeptin neurons [ 140 , 141 , 142 , 143 ]. It is not difficult to propose that estrogen signaling genes might impact heifer fertility and therefore could be proposed as both positional and functional candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that girls with obesity enter puberty at younger ages than girls with normal weight [ 98 ]. The adipokines leptin and adiponectin may play a role in the inverse association between menarche onset and weight status by modulating the hypothalamic–pituitary–gonadal axis [ 99 ]. Briefly, leptin activates the hypothalamus through secretion of the hormone kisspeptin to secrete gonadotropin releasing hormone.…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%
“…This hormone then activates the pituitary gland to produce follicle stimulating hormone and luteinizing hormone, resulting in the secretion of estrogen by the ovaries and, consequently, menarche onset. On the other hand, adiponectin inhibits the secretion of gonadotropin releasing hormone and delays puberty onset [ 99 ].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%